Reforming Justice: Unpacking the Pre-Judication and Post-Judicate Dynamics of the Sarpin Case in Law and Practice in Indonesia - Benny Sumardiana; Pujiyono Pujiyono; Irma Cahyaningtyas (Universitas Negeri Semarang, 2024)
This paper critically examines the Sarpin case within the context of Indonesia's criminal justice system, focusing on the legal reformation of pretrial procedures and their impact on the protection of suspects' human rights. Indonesia's criminal justice system adheres to the principle of presumption of innocence, which underscores the importance of safeguarding individual rights throughout the legal process. The introduction of the pretrial institution under the Criminal Procedure Code (KUHAP) has introduced significant shifts in judicial practices, particularly in evaluating coercive measures such as arrest, detention, and the termination of investigations. This research addresses three key questions: first, how pretrial procedures are regulated from the perspective of criminal law; second, how the reform of pretrial practices has been influenced by Judge Sarpin's landmark decision; and third, the broader implications of his ruling on the protection of human rights within the Indonesian criminal process. The paper utilizes a normative research method, analyzing relevant statutes and legal concepts through a statutory approach. In the Sarpin case, Judge Sarpin ruled that the investigation warrant used to initiate proceedings against Budi Gunawan was invalid, highlighting a critical legal interpretation of pretrial powers. This ruling not only questioned the procedural foundation of the case but also demonstrated the significant role of pretrial in defending the rights of suspects. Article 77 of KUHAP grants district courts the authority to examine the legality of coercive actions, providing a vital safeguard against potential abuses. The paper evaluates how Judge Sarpin's decision has reshaped legal practices in Indonesia, emphasizing its potential to reform both judicial attitudes and the protection of fundamental rights.